2021
DOI: 10.1002/fsn3.2103
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of β‐lactoglobulin with gum arabic: Effect of heat treatment and enhanced encapsulation efficiency

Abstract: Heat treatment is widely used in food industry. Proteins and polysaccharides as important natural polymers in food, under heat treatment, the interactions between them could mediate the conformation and functional properties of proteins. Thermally induced β‐lactoglobulin‐gum arabic complexes (β‐Lg‐GA) were fabricated, and the effect of heat treatment on physicochemical properties of the complexes was systematically investigated. The average particle size of β‐Lg‐GA complexes decreased with temperature increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…In order to explain this phenomenon, we may need to consider the following: heating promoted more nisin molecules dispersed in the EWP nanoparticle matrix and inhibited the aggregation of their crystals, thus promoting the formation of more amorphous complexes. Similar results have also been reported for biopolymer particles, which were formed by the heating of β-lactoglobulin-gum arabic complexes in the presence of epigallocatechin-3-gallate with enhanced encapsulation efficiency [42]. These findings suggest that the heating process promoted additional noncovalent interactions between EWP and nisin, ultimately enhancing the encapsulation of nisin within EWP nanoparticles.…”
Section: Xrd Analysis Of Nisin-loaded Ewp Nanoparticlessupporting
confidence: 86%
“…In order to explain this phenomenon, we may need to consider the following: heating promoted more nisin molecules dispersed in the EWP nanoparticle matrix and inhibited the aggregation of their crystals, thus promoting the formation of more amorphous complexes. Similar results have also been reported for biopolymer particles, which were formed by the heating of β-lactoglobulin-gum arabic complexes in the presence of epigallocatechin-3-gallate with enhanced encapsulation efficiency [42]. These findings suggest that the heating process promoted additional noncovalent interactions between EWP and nisin, ultimately enhancing the encapsulation of nisin within EWP nanoparticles.…”
Section: Xrd Analysis Of Nisin-loaded Ewp Nanoparticlessupporting
confidence: 86%
“…At higher temperatures, the hydrophobic interaction becomes stronger, which led to a more compact structure of the nanoparticles’ structure and the diameter becoming smaller [ 24 ]. In addition, higher temperatures might cause some compositions to separate from nanoparticles and the diameter to become smaller [ 25 ]. Some studies have demonstrated a similar change in β-lactoglobulin/pectin nanoparticle size with increasing temperature [ 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…chitosan, gum arabic and carboxymethylcellulose, interact with b-Lg in a similar manner to alginate. [58][59][60] Alginate further interacts with potato and soy proteins in a similar manner to b-Lg. 12,61 We suspect that the sticker-spacer network findings described here are transferable to other AP protein systems, laying the foundation for a global understanding of how to utilize complex coacervation in the future.…”
Section: Discussionmentioning
confidence: 99%